Validation of a Method to Measure the T2 Value from the Color Mapping by Hue Value - Hananouchi, Takehito; Nakayama, Makishi (Current Medical Imaging, 2023)
Background: Color mapping using quantitative MRI (Magnetic Resonance Imaging) is now being reported in various medical fields to be useful in showing tissue conditions and morphological perspectives. Specifically, T2 mapping, as one of the color mapping has been used to describe cartilage conditions in orthopedics. However, for orthopedic physicians in outpatient clinics, the color mapping shows only the colors on the mapping to patients without explaining their numerical values. Methods: Our study proposed an approach to measure T2 values based on the hue value converted from Red, Green, Blue information on the processed color map to address this issue. We evaluated the validity of our method with 25 subjects. Results: Our proposed method showed a good and high correlation coefficient (r = 0.9924, p < 0.0001), and the difference in the T2 values using dedicated software on the console of the MRI scanner and our method was small (its absolute value was approximately 1.5, p = 0.008). Conclusion: Therefore, we consider the proposed method is an alternative approach to show the T2 value when the color mapping is available.
Keywords: medical imaging